3D‐printed PMMA implant for gingival smile treatment through the VISTA technique: A report of a new approach. Issue 1 (10th January 2023) - de Castro, Luiz F.; de Andrade, Patrícia F.; Leite, Gabriel G.; de Andrade, Ana Júlia S.; Valentim, Gustavo L.; de Souza, Ernani T.
Abstract: Background: A gingival display higher than 3 mm is considered a characteristic of a gingival smile (GS). Several etiological factors have been associated to GS and for this reason various treatments have been proposed according to its etiology. The aim of this study is to present a case with an alternative technique to treat GS with minimally invasive vestibular incision subperiosteal tunnel access (VISTA) and polymethyl methacrylate (PMMA) implants for lip repositioning. Methods and Results: The patient, a 25‐year‐old woman diagnosed with excessive gingival exposure, had previously done botulinum toxin (BoNT) injections and did not like the result. She had a major subnasal depression and the upper lip would lodge in there during spontaneous smile. She was informed about all options of treatment and agreed to a lip repositioning installing a customized PMMA implant. Conclusion: This is the first study to our knowledge to present a case with use of a PMMA implant associated with the VISTA approach for lip repositioning and gingival smile correction. The results are encouraging, and the patient was satisfied with results accomplished by this technique. Key points: Why is this case new information? This is a new and innovative surgical approach for gingival smile with PMMA implants through a minimally invasive technique (VISTA). What are the keys to successful management of this case? Well‐defined presurgical planning and the presence of the upper lip lodging in the subnasal depression during spontaneous smile. What are the primary limitations to success in this case? Cases with vertical maxillary excess and those in which osteotomy/osteoplasty is indicated. It is a technique‐sensitive treatment dependent on the clinician's experience.